The role of autophagy-lysosomal pathway in motor neuron diseases. (31st October 2022) - Tedesco, Barbara; Ferrari, Veronica; Cozzi, Marta; Chierichetti, Marta; Casarotto, Elena; Pramaggiore, Paola; Mina, Francesco; Piccolella, Margherita; Cristofani, Riccardo; Crippa, Valeria; Rusmini, Paola; Galbiati, Mariarita; et al.
Abstract : Motor neuron diseases (MNDs) include a broad group of diseases in which neurodegeneration mainly affects upper and/or lower motor neurons (MNs). Although the involvement of specific MNs, symptoms, age of onset, and progression differ in MNDs, the main pathogenic mechanism common to most MNDs is represented by proteostasis alteration and proteotoxicity. This pathomechanism may be directly related to mutations in genes encoding proteins involved in the protein quality control system, particularly the autophagy-lysosomal pathway (ALP). Alternatively, proteostasis alteration can be caused by aberrant proteins that tend to misfold and to aggregate, two related processes that, over time, cannot be properly handled by the ALP. Here, we summarize the main ALP features, focusing on different routes utilized to deliver substrates to the lysosome and how the various ALP pathways intersect with the intracellular trafficking of membranes and vesicles. Next, we provide an overview of the mutated genes that have been found associated with MNDs, how these gene products are involved in different steps of ALP and related processes. Finally, we discuss how autophagy can be considered a valid therapeutic target for MNDs treatment focusing on traditional autophagy modulators and on emerging approaches to overcome their limitations.